Gender bias and digital financial services in South Asia : obstacles and opportunities on the road to equal access - Arora, Rashmi U. (Emerald points., 2020)
Several studies have shown that financial inclusion impacts poverty and income inequality and higher levels of financial inclusion lead to lower poverty and income inequality and promotes inclusive economic growth. However, the gender gap in access and usage of financial services remains pervasive across all the countries in South Asia. Patriarchal societies, low involvement of women in decision making, low empowerment of women, no voice in the family matters are some of the factors influencing women's financial access in the region. Although literature has developed on access to financial services in general, there is not much academic work available on access to digital financial services for women. Gender Bias and Digital Financial Services in South Asia: Obstacles and Opportunities on the Road to Equal Access examines access to financial services to women in general in South Asia and specifically their access to digital financial services.